Performance characteristics of low threshold current 1.25 μm type-II GaInAs/GaAsSb 'W'-lasers for optical communications. (30th June 2021) - Duffy, Dominic A; Marko, Igor P; Fuchs, Christian; Eales, Timothy D; Lehr, Jannik; Stolz, Wolfgang; Sweeney, Stephen J
Abstract: Type-II 'W'-lasers have made an important contribution to the development of mid-infrared laser diodes. In this paper, we show that a similar approach can yield high performance lasers in the optical communications wavelength range. (GaIn)As/Ga(AsSb) type-II 'W' structures emitting at 1255 nm have been realised on a GaAs substrate and exhibit low room temperature threshold current densities of 200–300 A cm −2, pulsed output powers exceeding 1 W for 100 µ m wide stripes, and a characteristic temperature T 0 ≍ 90 K around room temperature. Optical gain studies indicate a high modal gain around 15–23 cm −1 at 200–300 A cm −2 and low optical losses of 8 ± 3 cm −1 . Analysis of the spontaneous emission indicates that at room temperature, up to 24% of the threshold current is due to radiative recombination, with the remaining current due to other thermally activated non-radiative processes. The observed decrease in differential quantum efficiency with increasing temperature suggests that this is primarily due to a carrier leakage process. The impact of these processes is discussed in terms of the potential for further device optimisation. Our results present strong figures of merit for near-infrared type-II laser diodes and indicate significant potential for their applications in optical communications.